Strategi Burden & Salvage: Formula yuridik untuk terapi doktrinal, phobia pajak karbon - Bakir, Herman (Jurnal Hukum & Pembangunan, 2023)
This text introduces the burden & salvage doctrine, a formula providing an alternative path to develop a solid lex specialis within the realm of Pigouvian tax. It promotes a type of “juridical therapy” for the Indonesian government to overcome their excessive “fear” of carbon taxes, which had led them to surrender and revoke the program until the end of President Joko Widodo’s tenure Method: Data was gathered online using the World Wide Web’s search features to their fullest potential. Findings: Carbon tax should ideally be established by the legislation of the lex specialis type, characterized by the burden and salvage ideology. In this scheme, a carbon tax is essentially nothing more than a Pigouvian tax, not serving as a source of state revenue (unlike typical taxes). Vice versa, it serves as a long-term investment to guide society towards a modern existence characterized by a social life centred around a green economy, transportation, technology, and industry. The incurred costs will undoubtedly be substantial. Consequently, in the early stages of its implementation, it will “certainly” pose significant challenges for the government. This is because it involves the transformation of a nation—an issue of radical, fundamental, and comprehensive changes within a social structure. This seems unattainable in a nation ruled by a malevolent governmental system characterized by greed, selfishness, fascism, brutality, and corruption. The path will be smooth in a country where the government is a great philanthropist or an sinterklaas economie, providing significant funds and energy for sponsorship.